Assessment of biofungicides, Beauveria brongniartii and Metarhizium anisopliae against sugarcane white grub, Holotrichia serrata - Shanmugam, P S; Saravanan, N A; Tamilselvan, N (Indian Journal of Plant Protection, 2020)
Short communication